Association between Indoor PM10 exposure and acute respiratory infection among children under five - Serly Marisa Pataysia Sihotang; Hendra Dhermawan Sitanggang; Marta Butar Butar Butar; Fajrina Hidayati (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Acute Respiratory Tract Infection (ARI) is a major health problem in toddlers and remains a cause of high morbidity and mortality in Indonesia, including Jambi City. The incidence of ARI in toddlers is influenced by various risk factors, one of which is environmental factors, particularly indoor air quality. One such indoor air pollutant is PM10. In addition to PM10, other factors can influence the incidence of ARI, such as nutritional status, exclusive breastfeeding, the presence of smokers in the home, adequate ventilation, and the use of mosquito coils. Purpose: To analyze the association between indoor PM10 exposure and acute respiratory infection among children under five. Method: This study used an observational analytical design with a cross-sectional approach. The sample consisted of 90 respondents aged 6-59 months in the Putri Ayu Community Health Center working area in Jambi City, selected using a purposive sampling technique. Data were collected through PM10 levels measurements using a DAZ-400 Particle Counter and interviews using a questionnaire. Data analysis was performed using univariate, bivariate, and stratified methods using R software. Results: Results showed that children living in homes with PM10 levels that did not meet the criteria were at risk of developing ARI (PR = 1.63; 95% CI: 1.19-2.23; P = 0.027). After stratification, PM10 remained a risk factor in each stratum, but with ventilation as an effect modifier. Conclusion: Indoor PM10 exposure was significantly associated with ARI among children under five. Improving indoor air quality, reducing indoor pollutant sources, and strengthening household ventilation are recommended to reduce ARI-related risks.